Acute stress decreases bimanual psychomotor performance during resection of simulated brain tumors. (3rd June 2015) - Bajunaid, K; Winkler-Schwartz, A; Fares, J; Baggiani, M; Christie, S; Alotaibi, F; Al Zharni, G; Sabbagh, A; Azarnoush, H; Werthner, P; Delmaestro, RF
Abstract : Background: Objective methods to assess the influence of significant stress on neurosurgical bimanual psychomotor performance have not been developed. We utilized NeuroTouch, a virtual reality simulator, to answer two questions: 1) What is the impact of significant stress on bimanual psychomotor performance during the resection of a simulated tumor? 2) Does stress influence performance immediately following the stressful episode? Methods: Uncontrollable 'intraoperative' bleeding during one of the tumor resections resulting in simulated patient cardiac arrest served as the acute stressor. Six neurosurgeons, 6 senior and 6 junior neurosurgical residents and 6 senior medical students were studied. The evaluated advanced tier 2 metrics were efficiency index, ultrasonic aspirator path length index, suction coordination index and ultrasonic aspirator bimanual forces ratio. Results: The stress scenario significantly decreased the efficiency index of all groups and significantly decreased performance for many groups for suction coordination index and ultrasonic aspirator path length index. Performance in all advanced tier 2 metrics returned to pre-stress levels in post stress resection scenarios. Conclusions: Our results are consistent with the concept that acute stress initiated by severe intraoperative bleeding significantly decreases bimanual psychomotor performance during the acute episode but had no significant influence on immediate post stress operative performance.